Challenging professional ethics in covering the consequences of the Corona pandemic Understand the present and Exploring the post-crisis phase - بن دريس أحمد (International Journal of Social Communication, 2021)
The media coverage of the global health crisis has distinguished the contrast and the difference between understatement, intimidation, and sensitization, Media practices have emerged that have confirmed that the media need to understand the nature of the professional behaviour they must adopt to cover the consequences of the pandemic and convey everything related to it to the public. Coverage fluctuated between obfuscation and misinformation that is inconsistent with the public's right to the media on the one hand and media awareness and solidarity that shows a high sense of the mission entrusted to the media man, on the other hand. In this study, we look for ethical manifestations in media practice before and during the Corona crisis, and we try to foresee the future, to talk about the post-Corona world in the media. And we present some proposals for fair and unbiased media coverage, in compliance with professional ethical values in the media